2020
DOI: 10.1039/d0qo01175d
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free synthesis of 3-chalcogenyl chromones from alkynyl aryl ketones and diorganyl diselenides/disulfides mediated by PIFA

Abstract: 3-Selenyl/sulfenyl chromones/thiochromones were conveniently synthesized from the PIFA-mediated reactions between alkynyl aryl ketones bearing an ortho-methoxy/methylthio group and diorganyl diselenides/disulfides. This metal-free approach is postulated to first undergo the formation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…In our recent work, by using diselenides/disulfides as selenium and sulfur sources, we realized the synthesis of 4‐chalcogenylisocumarins [18] and 3‐chalcogenylchromones [19] via cascade annulation/organochalcogenylation mediated by hypervalent iodine reagents, i. e., (dichloroiodo)benzene (PhICl 2 ) and phenyliodine bis(trifluoroacetate) (PIFA). In continuation of our research on synthesis of various chalcogenylated heterocycles, we are interested at investigating whether the above protocol could be applied to the synthesis of the biologically interesting 4‐chalcogenylated isoxazoles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our recent work, by using diselenides/disulfides as selenium and sulfur sources, we realized the synthesis of 4‐chalcogenylisocumarins [18] and 3‐chalcogenylchromones [19] via cascade annulation/organochalcogenylation mediated by hypervalent iodine reagents, i. e., (dichloroiodo)benzene (PhICl 2 ) and phenyliodine bis(trifluoroacetate) (PIFA). In continuation of our research on synthesis of various chalcogenylated heterocycles, we are interested at investigating whether the above protocol could be applied to the synthesis of the biologically interesting 4‐chalcogenylated isoxazoles.…”
Section: Resultsmentioning
confidence: 99%
“…of PhICl 2 in acetonitrile (CH 3 CN) was stirred at room temperature for 30 min (entry 1, Table 1). Inspired by our another work describing the synthesis of 3‐chalcogenylchromones via PIFA‐promoted tandem chalcogenylation and cyclization of alkynyl aryl ketones, [19] we also attested the efficacy of phenyliodine diacetate (PIDA) and PIFA. However, the results showed that PIDA was ineffective and PIFA only led to the formation of product in trace amount (entries 2 and 3, Table 1), mainly because PIDA was less active for the reaction with 90% starting material recovered and PIFA was so potent for the transformation to give a complex mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang’s group realized the reaction of AgSCF 3 with methylthiolated alkynones for the synthesis of 3-trifluoromethylthiolated thioflavones with (NH 4 ) 2 S 2 O 8 as the oxidant at 80°C ( Wang L. et al, 2021 ). Du and Zhao et al reported the synthesis of selenyl/sulfenyl thioflavones with phenyliodine(III) bis(trifluoroacetate) (PIFA) as an oxidant ( Ai et al, 2020 ). Recently, Ye and Wu’s group realized an Ir-photocatalyzed radical relay reaction of methylthiolated alkynones and potassium metabisulfite in the presence of sodium methylsulfinate ( Liu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Du and Zhao et al . reported a regioselective cyclization of alkynyl aryl ketones mediated by PIFA [Bis(trifluoroacetoxy)iodo]benzene in the presence of organochalcogenides, affording several structurally diverse 3‐chalcogenyl chromones in reasonable yields [11b] …”
Section: Introductionmentioning
confidence: 99%